Aquatic and lion faced water sprouts - Ghosh, Ayan (Jio Institute, 2023)
During the time of its restoration in 2017, Flora Fountain was suffering from damage and leakage that interfered with the water flow. The restoration team led by architect Vikas Dilawari had to remove concrete to locate and create a map of the internal plumbing. They then enlisted the services of Burjoor Framji & Co., the city’s oldest plumbers, to repair the damaged plumbing and make the fountain fully operational when it was re-opened in 2019.